Islamic finance and COVID-19 recovery: the role Profit-Loss Sharing Contract - Aisyah Abdul-Rahman,; Gholami, Reza (Penerbit Universiti Kebangsaan Malaysia, 2020)
This note uncovers the beauty of Islamic finance via its Profit-Loss Sharing Contract (PLSC) as a financing tool in helping the economy and businesses to recover from COVID-19 economic crisis. PLSC is a contract that shares business risks between participants, while Interest-Based Contract (IBC) requires entrepreneurs to bear the entire business risks. Besides its fairness and justice in wealth creation and income distribution, past literature have shown that PLSC has been successfully adopted in various countries across industries. Redesign of mind-set and role from self-interest to common interest and from intermediaries to entrepreneurs are needed for the financial sector to embrace the benefits of PLSC towards achieving economic and societal sustainability.